Evaluasi Desain Aplikasi Delivery Menggunakan Metode System Usability Scale - Sidharta, Matthew Novan; Putri, Luh Arida Ayu Rahning (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 2 No 1 (2023): JNATIA Vol. 2, No. 1, November 2023DO - 10.24843/JNATIA.2023.v02.i01.p24, 2023)
Technology continues to develop from time to time and has been widely used to support various forms of services, such as delivery service. However, not every aspect can be fulfilled by this kind of application. The delivery application which is selected by researcher in this paper is disguised. The application under this research will be evaluated in terms of UI/UX design. The usability testing method that will be used in the evaluation process is the system usability scale. The result shows that the system usability scale’s score on the application is at 54,16. To improve the application performance, especially in terms of UI/UX, the application can be redesigned for the next research. Keywords: Delivery, UI/UX Design, Usability Testing, System Usability Scale